The estimation of genetic distance and discriminant variables on breed of Indonesian sheep by morphological analysis - Agus Suparyanto; T Purwadaria; Subandriyo . (Indonesian Center for Animal Research and Development (ICARD), 1999)
The morphological discriminant and canonical analyses were carried out to determine the genetic distance and discriminant variables between Indonesian breeds of thin tail sheep from Deli Serdang (North Sumatera), Ciamis and Garut (West Java) and fat tail sheep from Garahan and Pamekasan (East Java). The number of sheep randomly collected from farmers was 665 heads, while that from breeding station was 183 heads. Zoometrical variables studied were body weight, body length, wither height, chest depth, chest circumference, hip height, hip depth, hip circumference, tail length, tail width and tail thickness. SAS package program was used to analyze the data. Results from distribution mapping produced by canonical analysis and Mahalanobis distance (phenogram tree) showed that breeds are divided into two groups. The first group is thin tail sheep which consists of Ciamis, Garut and Sumatera, and the other is fat tail sheep which consists of Garahan and Pamekasan. The groups of Ciami and Garut were mixed by Garahan with 1.01 and 1.20%, respectively but were not contaminated by Pamekasan (0.00%). The highest similarity between individual inside the group was obtained from Sumatera (84.27%) due to the isolated flock. It was mixed more by Ciamis (7.87%) and Garut (5.62%) than Garahan (1.69%) and Pamekasan (0.50%). Results from canonical analysis also showed that body length, chest circumference, hip circumference, and body weight was less discriminant variables to determine the differences between breeds, while the most discriminant variables were obtained by tail length, tail width and tailthickness. Key words : Sheep, genetic distance, morphology